A psicanalise nas situações sociais críticas: uma abordagem grupal à violência que abate a juventude das periferias - Broide, Jorge (2006)
This research deals with the violence that assails the youth in big city suburbs. The theoretical reference used is the work of Freud and the Argentinean School of Psychoanalysis, and in particular, Enrique Pichon Riviére. Eight sessions of a working group were carried out in an institution which works with the problem of violence and which has a program for the formation of youth leaders in the Southern Zone of the city of São Paulo. Two youths from this group committed homicide in a common fight, starting with a conflict between gangs at a Friday night party, a typical case in the run down suburbs. They were not arrested. The institution invited us to coordinate the group whose task would be to discover the reason why some youths kill and others do not. Not only did the two youths in question take part in the working group but also others (many of whom had survived massacres), besides some intellectuals, managers and directors of the institution, more or less twenty people altogether. The working group was used as a research instrument in the social field, seeking the deepest links and the implicit and unconscious reasons for the violence that effects a large part of our youth. We hope that the conclusions will also be useful in the vocational training of professionals who work directly in this field, formulating public policies and social programs. The categories elaborated from the clinical material were: the territory of the suburbs, which portrays the everyday violence; the word, which relates its presence or absence relating to the lead up to the act; the processes of identification, which bring up family dynamics; and the difference between social classes which discusses the class conflict and social relations experienced by the youths